Using Nudges Theory to Improve the Efficiency of Decisions in Public Organizations Analytical Vision - Mohamed , Abdelrahim (The Arab Journal of Administration, 2023)
The nudge theory is launched by focusing on the behavioral aspect that helps in responding to development. This theory aims to improve the selection results. In the current reality, the institutions make a lot of efforts to direct their workers towards participation in many matters that are often in the interest of workers, but the responses are always weak or unwilling to participate. The experiences that applied this theory show that it contributed to improving the quality of decisions in several areas that were applied, which had an impact on the retirement policy in the United Kingdom, which resulted in an increase in pension savings rates, and had an impact on the policy of motivating the public to donate organs in Spain As the number of donors increased, as well as in the area of taxation in the United Kingdom, when this theory was applied, the country increased tax revenues. The formulation of the study problem was formulated in a question: To what extent does the nudge theory contribute to improving the quality options of decisions in public organizations? By analyzing the literature in this field and examining some experiences and analyzing it, the theory contributes to changing and improving employee behavior toward the decisions that the organization wants to take to achieve its goals. The study recommended the necessity of adopting nudging theory and educating employees about its concept and its impact on decision making.